Izročitev gradiva evidenc Inženirske zbornice Slovenije - Škofljanec, Jože (Moderna arhivistika, 2021)
Following changes in regulation, as well as in the information system used in register management at Slovene Chamber of Engineers, there appeared a need for archiving data from the older information system. In order to meet this need, register data needed to be transformed into a form suitable for submission to the archives, documentation on the format migration and additional documentation explaining the context of management of the registers until submission. The submission of the records was also used when forming template for the so-called additional professional and technical instructions. In addition, a software tool used to create submission information packages was tested. Finally, options were weighed regarding possible submission of certain identifiable personal data.
Keywords: archiving; arhiviranje; beseda; evidence; podatkovne zbirke; registers; relational databases; word